THE EVOLUTION OF HOMO ECONOMICUS - N. V. Komarovskaia (Vestnik MGIMO-Universiteta)
The article provides a review of the ways in which interdisciplinary research in modern economic thought gives a more realistic understanding of human behavior and economic decision making. On the one hand, economic imperialism drove wider application of economics methods across social sciences and brought about new interdisciplinary fields, such as law and economics, economic sociology, public choice theory, etc. On the other hand, the origin of behavioral economics, experimental economics, and neuroeconomics bridging psychology, neurobiology, and economics influences the change in the methodology used by the economics itself and fuels transformation of the model of rational economic behavior 'homo economicus', one of the central assumptions of the neoclassical economics. George Akerlof and Robert Shiller's animal spirits, prospect theory of Daniel Kahneman and Amos Tversky, research by Amartya Sen, Daniel McFadden, Vernon Smith, and other economists focusing on decision making either significantly limit, or supplement the homo economicus concept providing a deeper insight into the nature of human rationality. Behavioral economics has already become so strong as a separate discipline that it can be classified into two streams - Classical and Modern, and its main principles should be incorporated into a basic course of traditional economics. The achievements of behavioral economics yield higher quality of economic research and forecasting. Interdisciplinary approach to the human behavior studies and transformation of homo economicus offer new tools for the development policy making.